ANALISIS LITERASI KEUANGAN DIGITALISASI PADA MAHASISWA PERBANKAN SYARIAHDI UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Haryono Haryono; Khadijah Nurani (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study was to determine how to manage money in digital financial literacy for Islamic Banking students at UIN Sjech M. Djamil Djambek Bukittinggi and to determine the obstacles and opportunities for students to improve digital financial literacy for Islamic Banking students at UIN Sjech M. Djamil Djambek Bukittinggi. This study uses a qualitative method in which researchers will try to find data information in the field or research place, understand and interpret the data and then the data is processed to be able to conclude the final results of the study. Data collection techniques use observation, interview and documentation methods. As well as data analysis techniques in this study using data collection methods, data reduction, data presentation and drawing conclusions. The results of the study show that the Analysis of Digital Financial Literacy in Islamic Banking Students at UIN Sjech M. Djamil Djambek Bukittinggi consists of basic personal finance, cash management, credit and debt management, saving, investment, risk management. Of the six indicators, Islamic Banking students understand financial literacy very well.